Caminhos cruzados: o percurso trilhado pelas mulheres caxienses do curso de ciências físicas e naturais da Faculdade de Formação de Professores do ensino médio e a missão uspiana em Caxias-MA - Santos, Elizete (Universidade do Vale do Rio dos Sinos, 2018)
The creation of the Faculty of Teacher Training (FFPEM) at Caxias\Ma enabled the opening of new horizons for the city of Caxias and the region in the late 1960s. It is what the thesis "Cross paths: the trajectory of the Caxias women of the Course of Physical and Natural Sciences of FFPEM and the Uspian mission in Caxias/MA. Show the constitution of this historical project, political and educational, and the consequences of this process, that is, how the University of São Paulo (USP) insert in the educacional project in Maranhão, given the need to qualify human resources to meet this demand. In a first moment we want to show where our restlessness starts and we present the place of the woman in the society Maranhense and Caxiense, especially that coming of lower social layer. We then proceeded to analyze the political plan presented by the José Sarney Government in the 1960s to try to understand how the project was implemented and how it was continued. Especially in what refers to the female presence in the courses created in the period. We are very interested in this process to verify how the agreement signed between the Government of Maranhão and the University of São Paulo (USP) to teach classes in the different courses offered, was progressed. We also want to cross this information with the presence of women as students and then as teachers, from the teaching programs developed by the "uspian mission" that underpinned their training, to try to perceive their growth. In order to meet this main objective, in the first section we look for the historical context of Caxias throughout the XIX and XX centuries to make an analytical survey about its development, especially from the transition of the economic model agro-exporting to urban-industrial, bringing, in this more panoramic view, also the presence of women from distinct social classes and female living in the traditional context of the city; in the second section we look more closely at the transformations occurring in the historical and social field of Caxias, as well as the feminine look and action on these transformations; in the third section we approach the educational context of Caxias to verify if it was indeed destined to the elite of the city and what movements were made so that the education was directed also towards the qualification of the working population; in the fourth section our analysis focused on the political movements geared toward the implantation of higher education in the city, the articulations, the agreement with USP and its closure; in the fifth section we discuss the training bias of USP, the institution contracted to train the teaching staff that should work in Caxiense education. The research sites were, among others, the collection of the Center of Higher Studies of Caxias of the State University of Maramhão, the Historical and Geographical Institute of Caxias, etc. The documentary sources were constituted by the letters-reports produced by the agreed institution and the biographical ones by the 3 academics who did the course of Physical and Natural Sciences.
Keywords: História; Professoras maranhenses; Protagonismo feminino; Ensino superior; Missão Uspiana; History; Teachers from Maranhão; Female protagonism; Higher education; Uspiana Mission; ACCNPQ::Ciências Humanas::História